An investigation into the speaking-based needs of English Preparatory School students during remote learning - Ünlü, Muhammet Mustafa (İstanbul Sabahattin Zaim Üniversitesi, 2022)
Remote learning has been a part of English language education for a long time. However, it had not been practiced as an alternative to face-to-face learning until the breakout of the Covid-19 epidemic in 2020. Due to the sudden surge in case numbers, English preparatory schools in universities worldwide had to create remote learning environments for their students. Therefore, an in-depth needs analysis study has become crucial in order to determine the newly-altering needs of English preparatory school students. In this qualitative study, an embedded single case study design was preferred. Semi-structured interview forms were used to conduct interviews with 57 participants. In this study, descriptive and content analysis techniques were employed. Consequently, the following suggestions emerged. Firstly, authentic and spontaneous tasks must be used, and independent and personalized learner language should be encouraged. Secondly, LMS software should be improved to facilitate instructors' monitoring and responding capabilities. Thirdly, verbal in-class interaction and dynamics ought to be enhanced via collaboration, assisting learners must be assigned to groups, and cameras should be turned on. Finally, oral assessment tools such as presentation and participation rubrics must be used, the conditions of verbal exams should be ameliorated, and immediate feedback ought to be given after assessment.

Uzaktan eğitim, uzun süredir İngilizce eğitiminin bir parçası olmuştur. Ancak 2020 yılında Covid-19 salgınının patlak vermesine kadar bu kadar kapsamlı bir şekilde uygulanmamıştı. Vaka sayılarındaki ani artış nedeniyle dünya çapındaki üniversitelerdeki İngilizce hazırlık okulları, öğrencileri için uzaktan öğrenme ortamları oluşturmak zorunda kaldı. Bu nedenle, İngilizce hazırlık sınıfı öğrencilerinin yeni değişen ihtiyaçlarının belirlenmesi için derinlemesine bir ihtiyaç analizi çalışması önemli hale gelmiştir. Bu nitel çalışmada gömülü tek durum çalışması deseni tercih edilmiştir. 57 katılımcı ile görüşme yapmak için yarı yapılandırılmış görüşme formları kullanılmıştır. Bu çalışmada betimsel ve içerik analizi teknikleri kullanılmıştır. Sonuç olarak aşağıdaki öneriler ortaya çıktı. İlk olarak, özgün ve spontane görevler kullanılmalı, bağımsız ve kişiselleştirilmiş bir öğrenci dili kullanımı dil teşvik edilmelidir. İkinci olarak, eğitmenlerin gözlemleme ve yanıt verme yeteneklerini kolaylaştırmak için ÖYS yazılımı geliştirilmelidir. Üçüncüsü, işbirliği yoluyla sınıf içi sözlü etkileşim ve dinamikler geliştirilmeli, asistan öğrenciler gruplara atanmalı ve kameralar açılmalıdır. Son olarak sunum ve katılım rubrikleri gibi sözlü değerlendirme araçları kullanılmalı, sözlü sınavların koşulları iyileştirilmeli ve değerlendirme sonrasında anında geri bildirim verilmelidir.
Uzaktan öğrenim sürecinde İngilizce Hazırlık Okulu öğrencilerinin konuşma becerisine yönelik ihtiyaçlarının incelenmesi
Keywords: English Language Education; Remote Learning; Needs Analysis; Speaking-Based Needs; English Preparatory School Students; İngiliz Dili Eğitimi; Uzaktan Öğrenim; İhtiyaç Analizi; İhtiyaç Analizi; Konuşma Temelli İhtiyaçlar; İngilizce Hazırlık Okulu Öğrencileri